The use of centralised asset management companies in bank restructuring : a political economy review of experiences from the Asian financial crisis - Chang, Han Lian (2015)
This paper seeks to provide an alternative perspective from the conventional economic approach to explain the mixed results of publicly-owned asset management companies (AMCs) that were set up for bank restructuring purposes during the onset of the 1997 Asian Financial Crisis. This paper focuses on the political economy dynamics in the use of publicly-owned AMCs by Indonesia, Malaysia and Thailand. This paper hypothesizes that state strength is the key determinant of publicly-owned AMCs' success, as state strength allows the government to exert its political will to prevent sub-optimal outcomes, contrary to the typical scenarios where the Nash equilibrium for Pareto-optimal outcomes can only be achieved through repeated games (multiple crises). Using the criteria developed in the study, Malaysia's AMC, Danaharta, was deemed the most successful among the three countries (Indonesia, Malaysia and Thailand) at bank restructuring. From the case of Malaysia's Danaharta, the state was able to exert its strength to influence legislative action speed and policymaking consistency, as well as to safeguard against political or interest group pressures. Statistical evidence from the Worldwide Governance Indicators and the World Bank's Database of Political Institutions were able to provide corroboration with the hypothesis, and further discussion on the importance of state strength is available through the individual country case studies.